Pemberdayaan Dan Pengelolaan TOGA Sebagai Upaya Preventif Dan Promotif Pada Musim Pancaroba - Fandinata, Selly; Arifiyana, Djamilah; Dipahayu, Damaranie (Pusat Riset dan Inovasi Nasional, 2023)
Significant temperature changes make the body unable to adjust properly, which eventually leads to disease, affects the immune system, and increases the risk of developing viruses and bacteria. Empowerment of family medicinal plants in the cultivation and utilization of TOGA can be a way to overcome these problems, especially in the city of Surabaya. The purpose of this community service is to increase public understanding of the efficacy of TOGA and to create facilities for nature conservation, especially the cultivation of TOGA greenery. The form of community service activities is providing education, giving and planting TOGA, and monitoring TOGA maintenance. The resulting output is increasing public understanding of the efficacy of TOGA and creating facilities for nature conservation, especially cultivating reforestation for special TOGA gardens (Kencur, turmeric, temulawak, and binahong) so that they can help realize preventive and promotional communities in overcoming disease problems that often arise during the transition season.